BOLLYWOOD MOVIES IN INDONESIA IN THE PRESPECTIVE OF INDIA’S SOFT DIPLOMACY - Ana Rizkia Umami (HI 16 UMY 109, 2016)
*109 India is a state that has so many cultures. One of the cultures is Bollywood. Bollywood movie contains the culture of India. India’s government applies Bollywood movie as the soft diplomacy to Indonesia. The Bollywood fever in Indonesia is so booming. There are some facts stated that India and Indonesia have good relation since the first India’s traders came to Indonesioa. They brought India’s culture to Indonesia. This undergraduate thesis will analyze the reasons behind India’s government in applying the Bollywood movie as soft diplomacy to Indonesia. It involves cultural diplomcy, national interest, and decision making process concepts. Firstly, the paper will prove that the reason of India’s government decision to apply Bollywood movie as soft diplomacy to Indonesia because it has values of culture, art, religion, morals, knowledge and other customs of India. Secondly, it is because Bollywood got positive responses from the International public. Bollywood movies increased gradually and India’s government saw this as the opportunity to get its economy and spread the culture. Keywords: Bollywood Movie, India, Indonesia, Soft Diplomacy, National Interest, Foreign Policy, Culture, Economy